Effects of laws expanding civilian rights to use deadly force in self-defense on violence and crime: a systematic review - Yakubovich, AR; Degli Esposti, M; Lange, BCL; Melendez-Torres, GJ; Parmar, A; Wiebe, DJ; Humphreys, DK (American Public Health Association, 2021)
Background. Since 2005, most US states have expanded civilian rights to use deadly force in self-defense outside the home. In most cases, legislation has included removing the duty to retreat anywhere one may legally be, commonly known as stand-your-ground laws. The extent to which these laws affect public health and safety is widely debated in public and policy discourse.